Experimental and numerical study of the heating profile of a solar oven applied to drying (Research, Society and Development, 2020)
Among food preservation techniques, drying can be highlighted. However, this is an operation that demands high energy consumption and can be made possible by applying an alternative non-polluting and inexhaustible energy source, such as solar energy. A device applied to dry that operates from the capture of solar rays is the solar oven. Reflective objects reflect the sun's rays into the interior of this dryer, providing an increase in the temperature of the air contained in the oven, for later application as drying air. To better understand the operation of this dryer, several authors have been studying it through computer simulations. Considering the above, the objective of this work is to carry out an experimental and numerical study of the heating of a solar oven. The experiment consisted of exposing the oven to sunlight and continuously recording ambient temperature values and in different positions on the equipment. The mathematical model used consists of individual energy balances for each component of the dryer, and the calculation of the heat transfer coefficients in convective form and by radiation was based on works in the literature. The model was implemented in the free software Scilab®, using the lsoda solver in the ODEPACK package and the experiments were developed at UFTM in Uberaba - MG. The results showed that the modeling approach employed was efficient in predicting the thermal behavior of the dryer, which reached temperatures suitable for drying (Ts* = 82oC) using only solar energy.